Sacred Sustainability: Ancient Traditions and Modern Sustainable Tourism in Kumbh Mela & Char Dham - Naresh Chandra Tripathi; Abhilash Dubey; Ria Agarwal (AG Volumes, 2026)
In India, pilgrimage tourism is a significant fusion of tradition, culture, and religion. Every year, pilgrimage tourism boosts the Indian economy by bringing millions of devotees to sacred locations, but it also puts tremendous strain on the country’s natural and cultural resources. Two of India’s most respected pilgrimage traditions, the Kumbh Mela and the Char Dham Yatra, have attracted millions of followers for millennia, demonstrating the intricate relationship between society, culture, and religion. Despite having their historical roots in spiritual practice, these gatherings also represent sustainability concepts that have developed from antiquated customs to modern management techniques. This study explores how traditional ecological wisdom like, seasonal timing, minimalist pilgrim lifestyles, and community-based resource sharing has converged with contemporary innovations like waste management systems, digital crowd control, renewable energy integration, and heritage-sensitive infrastructure in the Kumbh Mela and Char Dham Yatra. The paper illustrates how both pilgrimage gatherings have changed to meet infrastructural demands, environmental concerns, and the difficulties of mass tourism through the use of historical narratives, policy documents, and case studies from recent iterations of both events. The study makes the case that a robust model for religious tourism around the world can be achieved by fusing traditional cultural norms with contemporary ecological standards. The Kumbh Mela and Char Dham Yatra show how faith-based tourism can be a potent tool for both ecological stewardship and cultural preservation by maintaining spiritual holiness while reducing environmental damage.